Application of a Sn4+ doped In2S3 thin film in a CIGS solar cell as a buffer layer. Issue 1 (4th November 2019) - Kim, SeongYeon; Mina, Md. Salahuddin; Kim, Kiwhan; Gwak, Jihye; Kim, JunHo
Abstract : As a Cd-free buffer, In2 S3 buffer has been used in Cu(In, Ga)Se2 (CIGS) solar cells. Abstract : As a Cd-free buffer, In2 S3 buffer has been used in Cu(In, Ga)Se2 (CIGS) solar cells. To increase the carrier density of the In2 S3 buffer, we doped Sn 4+ into the buffer layer, which acted as an electron dopant in the In2 S3 buffer layer. It was found that an optimal Sn 4+ doping into the In2 S3 buffer enhanced the power conversion efficiency of the CIGS solar cell. The deep defect states were reduced at both the bulk and surface of the CIGS solar cell by Sn 4+ doping. The capacitance–voltage ( C – V ) charge density profile showed an increased depletion width in CIGS with the Sn 4+ doped In2 S3 buffer, thus implying an increase in the electron charge density in the Sn 4+ doped In2 S3 buffer. At 3% Sn 4+ doping into the In2 S3 buffer, the power conversion efficiency (PCE) was increased from 10.05% (CIGS solar cell with non-doped In2 S3 buffer) to 14.52%.